Identifikasi dan Kuantifikasi Kadar Fenol Total Jahe (Zingiber officinale) Ekstrak sebagai Tahap Pendahuluan untuk Pengembangan Salep Topikal - Putri Jati Utami; Triasari Oktavriana; Prasetyadi Mawardi; Utiya Nur Laili; Larisa Sabrina Rahadiyanti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Ginger (Zingiber officinale) is traditionally used for inflammatory conditions and is currently being developed as a topical agent for psoriasis, with therapeutic effects largely attributed to phenolic constituents such as gingerols and shogaols. Prior to formulating ginger extract into 5% and 10% salves, qualitative confirmation and quantitative determination of phenolic content are essential to ensure adequate active marker levels. This study aimed to identify and quantify the total phenolic content of ginger extract intended for topical salve development. Qualitative identification used the ferric chloride (FeCl3) 1% test. Quantitative determination employed the Folin–Ciocalteu method with gallic acid as reference standard. Approximately 0.2 g of extract was dissolved in methanol p.a., reacted with 7.5% Folin–Ciocalteu reagent and 1% NaOH, and absorbance measured at λmax in triplicate. Total phenolic content was expressed as % gallic acid equivalents (GAE). The FeCl3 test produced a distinct color change confirming phenolic compounds. λmax was 733 nm with operating time 44–46 minutes. The calibration curve was linear (Y = 0.0652 + 0.00706X; r = 0.9991). Mean total phenolic content was 7.47 ± 0.36% GAE (74.70 ± 3.63 mg GAE/g extract; CV = 4.86%, meeting the < 5% precision criterion). The value measured by the Folin–Ciocalteu method reflects the total reducing capacity of the extract, which is primarily attributable to phenolic constituents such as gingerols and shogaols, although contributions from other reducing substances cannot be excluded. This batch-specific value provides a baseline reference qualifying the extract as the candidate active ingredient for subsequent 5% and 10% topical salve formulation, with confirmatory chromatographic identification recommended prior to scale-up.